The Role of the National Police in Prioritizing Restorative Justice in Resolving Insult and Defamation Cases Based on Circular Letter from the Chief of Police Number: SE/2/11/2021: Case Study at the Deli Serdang Police Criminal Investigation Unit in Lubuk Pakam - M.H. Samosir, Jonner; Zarzani, T. Riza (PT. Multidisciplinary Press Indonesia, 2025)
The purpose of this paper is to study the concept of restorative justice in the Police of the Republic of Indonesia (Polri) and also to observe how the Police react, interact as well as their techniques in responding to complaints from the general public. In this paper, a case study is carried out by conducting a study of the case LP/B/880/I/2002/PKT/North Sumatra Police Date 17 May 2022. The case approach is conducted by studying the views and doctrines in legal science, which will find ideas that can give rise to legal understandings, legal concepts and legal principles that are relevant to the issue faced.